2020
DOI: 10.1108/ijchm-04-2020-0345
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social capital and knowledge sharing intention on restaurants’ new product development

Abstract: Purpose Using social capital theory, this study aims to investigate internal social capital (ISC) and external social capital (ESC) as determinants of knowledge sharing intention (KSI) and new product development (NPD) in high-end restaurants. Design/methodology/approach A theoretical model is developed and tested using data collected from 523 respondents (owners/proprietors, partners and managers) from high-end restaurants in Karnataka, India. Partial least square structural equation modeling is used to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 91 publications
(174 reference statements)
0
20
0
1
Order By: Relevance
“…By doing so, the ineffective dyadic negotiation can be formally transformed into a more effective three-party knowledge exchange between the knowledge holders, receivers and the manager. These suggestions can be incorporated with the improvement of human resource management practices, focusing on internal processes supporting cooperative behaviors within hospitality firms (Chowdhury et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By doing so, the ineffective dyadic negotiation can be formally transformed into a more effective three-party knowledge exchange between the knowledge holders, receivers and the manager. These suggestions can be incorporated with the improvement of human resource management practices, focusing on internal processes supporting cooperative behaviors within hospitality firms (Chowdhury et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, for most hotel employees, sharing knowledge is not a mandated responsibility that can be formally coerced or supervised by managers (Cooper, 2006). Instead, their willingness to share knowledge may depend on specific contextual antecedents (Lombardi et al , 2019; Chowdhury et al , 2020). For instance, to improve teamwork performance, some conscientious employees may share knowledge about interpersonal collaboration with co-workers (Yang, 2004a, 2009).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For example, Kim and Shim (2018) identify lack of trust as one of the factors that hinder employees' intention to share their knowledge in a given organization. In some Asian countries, fear of penalty inhibits employees from sharing their knowledge (Chowdhury, Prayag, Patwardhan, & Kumar, 2020). Personal competitiveness among employees is another factor that inhibits them from knowledge sharing.…”
Section: Introductionmentioning
confidence: 99%
“…Although scholars and practitioners consider high-performing employee turnover to be a critical organizational phenomenon, there is still a lack of understanding of this phenomenon, particularly in the hospitality industry. Few longitudinal studies have looked at the effect of turnover on social capital and organizational outcomes (Dess and Shaw, 2001;Chowdhury et al, 2020). Some studies have found a link between high-performing employee turnover and company performance, while others have not (Shi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%